Effect of Working Capital, Debt Policy and Firm Size on Firm Value with Profitability as an Intervening Variable - Hermanto Hermanto; Elisa Aryani (Institute of Computer Science (IOCS), 2021)
The purpose of this study is to determine the effect of working capital (WCTT), debt policy (DER) and firm size on firm value with profitability as an intervening variable. The population taken is the food and beverage sub-sector entities listed on the Indonesia Stock Exchange from 2016 to 2020 totalling 34 entities. Sampling with purposive sampling technique through certain standards, samples obtained amounted to 70 samples (14 entities with 5 years of research). This study has the result that working capital, debt policy, profitability and firm size have a simultaneous and significant impact on firm value. Working capital, debt policy and firm size have a simultaneous and significant impact on profitability. Working capital has an individual positive impact on firm value and has an individual positive impact on profitability. debt policy has no individual impact on firm value and no individual impact on profitability. Firm size has no individual impact on firm value and no individual impact on profitability. Profitability has an individual positive impact on firm value. Research findings where if an entity wants to increase the value of the company, it must pay attention to working capital, debt policy and company size and increase the profits generated.